Pela and Gandong in Maluku, Indonesia: Fostering Interfaith Dialogue and Community Cohesion between Diverse Religious Communities - Sabara; Amiruddin; Muhammad Nur; Nensia; Utari, Tria Ina; Amin, Saifuddin (Journal of Al-Tamaddun, 2025)
Pela and Gandong serve as cultural foundations that facilitate cohesion between Islamic and Christian communities in Maluku, which occupy distinct geographical regions. This article intends to elucidate the bond of brotherhood engendered by the Pela, or customary agreements, established between Islamic and Christian villages in Maluku. Additionally, it will examine the manifestations of interreligious harmony reflected in the construction of mosques and churches. This research employs a case study methodology with a bounded system approach, focusing on the Pela relationship between Hitu Lama village (Islam) and Galala village (Christianity). This relationship serves as a representative example in illustrating the mechanisms of Pela in the context of mosque and church construction. Established in 1959, the Pela relationship between Hitu Lama and Galala villages reinforces brotherhood through shared traditions and historical narratives that transcend religious divides. A notable example of this collaboration is the joint construction of a mosque and church, which both communities regard as shared properties. This research aims to contribute to strategies that bolster Maluku’s reputation as a laboratory for harmony through the practice of establishing places of worship rooted in the Pela relationship. The construction of mosques and churches represents a culmination of harmonious events and stands as a model of the positive relations between Muslims and Christians in these two villages.